The vascular response to vasodilators is related to the membrane content of polyunsaturated fatty acids in hypertensive patients. Issue 5 (May 2015) - Colussi, GianLuca; Catena, Cristiana; Dialti, Valeria; Mos, Lucio; Sechi, Leonardo A.
Abstract : Objective: Abnormal vascular reactivity contributes to the pathophysiology of hypertension and hypertension-related organ damage. As the dietary content of fatty acids may affect the vascular responses, we investigated the relationship of endothelium-independent and endothelium-dependent vasodilation with the fatty acid composition of red blood cell (RBC) membranes in hypertension. Methods: In 45 uncomplicated hypertensive patients, we measured the content of fatty acids in RBC membrane as a marker of dietary intake of fatty acids, and the vasodilatory response of the brachial artery to both nitrate-donor compound (nitrate-mediated vasodilation, NMD) and postischemic reactive hyperemia (flow-mediated vasodilation, FMD). Results: Baseline diameter of the brachial artery was significantly lower and vasodilatory response to NMD was significantly greater in patients with RBC membrane polyunsaturated-to-saturated fatty acid (PUFA/SFA) ratio above the median of the distribution than in patients with PUFA/SFA ratio below the median, whereas no difference was observed in FMD. n −3 PUFA and n −6 PUFA content, and the PUFA/SFA ratio of RBC membranes were related inversely with brachial artery diameter and directly with maximal NMD, whereas no relationship of fatty acid components of RBC membrane with FMD was observed. Multivariate analysis that included demographic, anthropometric, clinical, and biochemical variables indicated that the RBC membrane PUFA/SFA ratio was an independent determinant of brachial artery diameter and NMD response. Conclusion: The endothelium-independent brachial artery vasodilation is independently related to the PUFA content of RBC membranes in patients with hypertension. This suggests the possible benefits of PUFA-enriched diets on the regulation of vascular tone and blood pressure in these patients. Abstract : Supplemental Digital Content is available in the text